FAKTOR-FAKTOR PERKEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) BERBASIS EKONOMI KREATIF DI KABUPATEN OGAN KOMERING ULU - Tuti Tri Handayani; Rini Apriyani (KOLEGIAL, 2020)
The results of this study indicate that the multiple linear regression equation Y = 0.972 + 0.275X1 + 0.687X2 + 0.077X3. The correlation value (R) between the variable lack of capital (X1), the weak human resource variable (X2), and the weak business network and market penetration variable (X3) to the micro economic small and medium business development creative variable (Y) is 0.902. This value shows that the correlation (R) between the variable lack of capital (X1), veriabel weak human resources (X2), and the weak variables of business networks and market penetration (X3) to the variable development of micro small and medium creative economy (Y) are very strong. Based on the t test with a ttable of 1.996, it shows that the variable lack of capital (X1) and the weak variable of human resource quality (X2) have a partial effect on the development of micro small and medium scale creative economy (Y). Whereas the weak variables of business networks and market penetration (X3) do not have a persial effect on the development variables of micro small and medium-sized creative economy (Y).